Pyoderma gangrenosum: current state of the problem - Uladzimir P. Adaskevich (ZAO "Consilium Medicum", 2021)
Pyoderma gangrenosum (PG) is a rare neutrophilic dermatosis that presents with rapidly developing, painful skin ulcers hallmarked by undermined borders and peripheral erythema. Epidemiological studies indicate that the average age of PG onset is in the mid-40s, with an incidence of 310 cases per million person-years. PG is often associated with a variety of other immune-mediated diseases, most commonly inflammatory bowel disease and rheumatoid arthritis. The cause of PG is not well understood, but PG is generally considered an autoinflammatory disorder. Studies have focused on the role of T cells, especially at the wound margin; these cells may support the destructive autoinflammatory response by the innate immune system. PG is difficult to diagnose as several differential diagnoses are possible; in addition to clinical examination, laboratory tests of biopsied wound tissue are required for an accurate diagnosis, and new validated diagnostic criteria will facilitate the process. Treatment of PG typically starts with fast-acting immunosuppressive drugs (corticosteroids and/or cyclosporine) to reduce inflammation followed by the addition of more slowly acting immunosuppressive drugs with superior adverse event profiles, including biologics (in particular, anti-tumour necrosis factor agents).